Original paperAnalysis of the dynamics of vitamin D status in the population of the Lodz region – a preliminary report - Bogaczewicz, Jarosław; Sysa-Jędrzejowska, Anna; Karczmarewicz, Elżbieta; Płudowski, Paweł; Woźniacka, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction: Despite the ease of exposure to solar radiation, as well as oral supplementation with vitamin D, several findings still indicate the presence of the problem of insufficient supply of the organism with vitamin D in many populations. Aim: To analyse the dynamics of changes of the vitamin D status in individuals of the population of the Lodz region depending on recreational exposure to solar radiation, and to determine the risk of vitamin D insufficiency. Material and methods: Three measurements of the concentration of 25(OH)D3 were performed: (1, baseline) within 2 weeks from the last exposure to solar radiation, (2) after 8 weeks, but not before September, (3) after 16 weeks. Measurements were performed with an automated method of the electrochemiluminescence assay under the DEQAS control system (vitamin D external quality assessment scheme). Results: At baseline, the recommended vitamin D level was found in 36.67%, hypovitaminosis in 56.67%, and deficiency in 6.67% of individuals. After 8 weeks the recommended level was ascertained in 16.67%, hypovitaminosis in 63.33%, deficiency in 16.67%, and deficit in 3.33% of persons. After 16 weeks the recommended level was observed in 6.67%, hypovitaminosis in 36.67%, deficiency in 50.00%, and deficit in 3.33% of persons. The concentration of 25(OH)D3 was significantly lower after 8 weeks in comparison to the baseline level (p < 0.0001). The decrease in the concentration after 16 weeks was significantly lower in comparison to the baseline value (p < 0.0001), as well as to those of the second measurement – after 8 weeks (p < 0.0001). The risk for low vitamin D level (< 30 ng/ml) after 16 weeks was more than twice as high as within the baseline period of exposure to solar radiation (OR = 2.79, p < 0.01). Conclusions: The low concentration of vitamin D after 8 and 16 weeks after recreational exposure to solar radiation and the increased risk for vitamin D insufficiency underline the rationale of the use, especially in winter months, of oral vitamin D supplementation.